Effect of parylene C coating on the antibiocorrosive and mechanical properties of different magnesium alloys; Applied Surface Science; Vol. 427, Pt. A - Surmeneva M. A. Maria Alexandrovna; Vladesku A. Alina; Kotrut M. K. Mikhay Kosmin; Tyurin A. I. Aleksandr Ivanovich; Pirozhkova T. S. Tatjyana Sergeevna; Shuvarin I. A. Ivan Aleksandrovich; Elkin B. Bentsian; Oehr C. Christian; Surmenev R. A. Roman Anatolievich (2018, 2018)
Title screen